Ahistorical Teleosemantics: An Alternative to Nanay. Issue 2 (June 2017) - Bauer, Mark
Abstract: The dominant view in teleosemantics is that semantic functions are historically determined. That reliance on history has been subject to repeated criticism. To sidestep such criticisms, Nanay has recently offered an ahistorical alternative that swaps out historical properties for modal properties. Nanay's ahistorical modal alternative suffers, I think, serious problems of its own. I suggest here another ahistorical alternative for teleosemantics. The motivation for both the historical view and Nanay's is to provide a naturalistic basis to characterize some item as possessing a function independent of its actual performance and, thereby, provide a grip on intentional inexistence and misrepresentation. I suggest that attending to the logic of mechanistic explanation suffices to provide the sought for naturalistic basis. The key advantage to the approach offered here is its relative parsimony: unlike its alternatives, it requires no substantive existential commitments, for example, commitments to natural selection, copying relations, or fitness‐enhancing modal properties, to naturalize semantic content.